EFL Students’ Reading Preferences Based on Gender: A Study of Perceptions among EFL Learners of Mulawarman University - Dr. Istanti Hermagustiana, MA; Dr. Yuni Utami Asih, M.Pd; Titis Tustika Putri Indriyani; Ida Wardani (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2026)
This study explores the perceptions of English as a Foreign Language (EFL) students regarding their reading preferences at the English Department of Mulawarman University. Focusing on gender differences, the research aims to understand how male and female students perceive their reading interests. Using a qualitative case study design, six sixth-semester students from English Language Education Program at Mulawarman University were selected through stratified purposive sampling. Semi-structured interviews were conducted to collect in-depth data on students’ views of reading for pleasure and their references in genre and reading habits. Thematic analysis revealed that students perceive reading as both an academic necessity and a personal interest, with noticeable gender-related patterns. Female students showed a balance preference for fiction and non-fiction genre, while male students leaned towards fiction. These preferences are shaped by individual interests, emotional engagement and exposure to various reading materials. Findings contribute to the understanding of how gender influences reading behavior among EFL learners.